The Relationship Between ERCC1 Expression and Clinical Outcome in Patients With FIGO Stage I to Stage II Uterine Cervical Adenocarcinoma. Issue 8 (1st November 2011) - Hasegawa, Kiyoshi; Kato, Rina; Torii, Yutaka; Ichikawa, Ryoko; Oe, Shuko; Udagawa, Yasuhiro
Abstract : Objective: Several studies have suggested that excision repair cross-complementation group 1 (ERCC1), a protein involved in nucleotide excision repair, is associated with resistance to platinum agent-based chemotherapy or chemoradiotherapy with platinum agents in various types of cancer. Herein we evaluated ERCC1 protein expression in uterine cervical adenocarcinoma and the relationship between this expression, clinicopathological factors, and clinical outcome, particularly in patients receiving adjuvant cisplatin-based chemotherapy or chemoradiotherapy with cisplatin. Methods: Thirty-six patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB to stage IIB cervical adenocarcinoma who underwent radical hysterectomy were evaluated. Excision repair cross-complementation group 1 protein expression was examined by immunohistochemistry in tumor tissues. The relationship between ERCC1 expression levels and clinicopathological factors (age, FIGO stage, histological grade, tumor size, vascular invasion, cervical stromal invasion, and lymph node metastases) and prognosis was evaluated. Results: No significant differences between ERCC1 expression levels and clinicopathological factors were observed. The patients in the ERCC1 high-expression group (n = 7) experienced significantly worse disease-free survival than the patients in the ERCC1 low-expression group (n = 29; P = 0.005). Among the 25 patients who received cisplatin-based chemotherapy or chemoradiotherapy with cisplatin, those with high ERCC1 expression (n = 5) also experienced significantly worse disease-free survival than those with low ERCC1 expression (n = 20; P = 0.002). Moreover, univariate and multivariate analyses revealed that high ERCC1 expression was an independent prognostic factor in patients receiving cisplatin-based chemotherapy or chemoradiotherapy with cisplatin. Conclusions: This is the first analysis of the association between ERCC1 expression and clinical outcomes in patients with uterine cervical adenocarcinoma. High ERCC1 protein expression was revealed to be associated with worse disease-free survival in the patients who received adjuvant cisplatin-based chemotherapy or chemoradiotherapy with cisplatin and was shown to be an independent prognostic factor. Further evaluation with a larger number of patients is required to confirm these preliminary observations.